If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = x + 13 Reorder the terms: 7 + -3x = 13 + x Solving 7 + -3x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -3x + -1x = 13 + x + -1x Combine like terms: -3x + -1x = -4x 7 + -4x = 13 + x + -1x Combine like terms: x + -1x = 0 7 + -4x = 13 + 0 7 + -4x = 13 Add '-7' to each side of the equation. 7 + -7 + -4x = 13 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 13 + -7 -4x = 13 + -7 Combine like terms: 13 + -7 = 6 -4x = 6 Divide each side by '-4'. x = -1.5 Simplifying x = -1.5
| x+114=84+x | | (j/6)-9=5/6 | | 8x-33=5x+27 | | 18=5x+4x | | 2h-6/6=2/3 | | x/4-12=7 | | ABD=(5y+1)180 | | -4(x-9)=-5x | | -17x=-2014 | | 4+(-10)= | | 10=5+2n-3 | | ABD=(5y+1) | | z+8=-50 | | 3(2x-4)+x/2=1 | | -2f(2f-4)=-4(-f+2) | | x+141=x+61 | | -14x=0 | | y^2-6y+13=0 | | x^3-3x^2+4x+8=0 | | 8=3n+n | | .5(t+7)=32 | | 2(3x+4)-4=9x+4-3x | | 15m+22=-7 | | 45/-3-6= | | 32h=128 | | z-4=1.4 | | 17=1-4m-4m | | 12-6x= | | 5(x+4)-(5x+20)=0 | | 4x-5+12=10x-7-3x+9 | | 33=-2x+5x+9 | | 9(5-k)+7=-7(k-4)-5 |